Requirements towards CIPP and WHL resin linings for pressure applications with respect to American standards as well as Polish standard PN EN ISO 11298-4 and their impact on the scope of strength calculations - Parka, Anna; Lisowska, Justyna (Instal, 2023)
The article discusses the basic requirements towards CIPP and WHL resin linings for pressure applications according to American standards ASTM F1216, ASTM 1743 and ASTM 2019 as well as Polish standard PN EN ISO 11298-4. Peculiar attention was paid to the rules regulating the average and minimum thicknesses of the above mentioned linings after complete cure and the minimum cope of their strength calculations depending on the assumed classes. The reasons for not suggesing the ring stiffness of these linings were also explained. Except this, the doubts regarding the procedure of establishing the long term values of their mechanical parameters were presented. The necessity of assuming different values of creep coefficient was poined out too. Finally, the article raises an issue related to reasonable thicknening of CIPP or WHL linings in order to achieve the effects typical to reconstruction instead of renovation process.
Keywords: trenchless renewal; pressure linings; CIPP; WHL